2002
DOI: 10.1152/japplphysiol.00461.2002
|View full text |Cite
|
Sign up to set email alerts
|

Aging induces muscle-specific impairment of endothelium-dependent dilation in skeletal muscle feed arteries

Abstract: . Aging induces muscle-specific impairment of endothelium-dependent dilation in skeletal muscle feed arteries. J Appl Physiol 93: 1685-1690, 2002; 10.1152/ japplphysiol.00461.2002.-We tested the hypothesis that aging decreases endothelium-dependent vasodilation in feed arteries perfusing rat skeletal muscle. In addition, we tested the hypothesis that attenuated vasodilator responses are associated with decreased endothelial nitric oxide synthase (eNOS) and superoxide dismutase-1 (SOD-1) expression. Soleus fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
123
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(143 citation statements)
references
References 29 publications
16
123
4
Order By: Relevance
“…Previous studies have indicated that NO-mediated endothelial function declines with advancing age (26,43,49), and recent reports have shown a similar impairment in endothelium-mediated vasodilation in the coronary microvasculature (7,21). In the present study, we have demonstrated for the first time an age-induced decline in flow-induced NO production, as evidenced by diminished DAF fluorescence in isolated coronary arterioles of aged rats (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have indicated that NO-mediated endothelial function declines with advancing age (26,43,49), and recent reports have shown a similar impairment in endothelium-mediated vasodilation in the coronary microvasculature (7,21). In the present study, we have demonstrated for the first time an age-induced decline in flow-induced NO production, as evidenced by diminished DAF fluorescence in isolated coronary arterioles of aged rats (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…This may represent a reduction in the reserve capacity of one or more vasoregulatory pathways (i.e. endothelium-independent dilation) in preference to dilatory function per se as reported by others (Muller-Delp et al, 2002b;Woodman et al, 2002). The combination of these impaired vasoregulatory mechanisms is likely to require higher strength contractions to increase arteriolar flow above resting values and, importantly, will significantly compromise the reserve capacity to increase arteriolar flow during maximal exercise.…”
Section: Mechanisms Of Microcirculatory Dysfunctionmentioning
confidence: 90%
“…For example, aging is associated with reductions in functional sympatholysis (Dinenno et al, 2005;Parker et al, 2007), myogenic control (Muller-Delp et al, 2002a), and contraction-induced rapid vessel relaxation (Carlson et al, 2008). Moreover, endothelium-dependent vasodilation is impaired (Muller-Delp et al, 2002b), with the dysfunction likely occurring preferentially in arterioles supplying oxidative but not glycolytic muscles (Woodman et al, 2002). While several discrete signaling pathways contribute to the endothelium-dependent regulation of vascular tone, NO appears to play a principal role, particularly in oxidative muscles (Hirai et al, 1994).…”
Section: Mechanisms Of Microcirculatory Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Power analyses indicate that a doubled sample size is required to achieve statistical significance in this instance. Furthermore, we studied the vastus lateralis alone; therefore, our results are only reflective of a mixed fiber type muscle bed and do not rule out the possibility that vascular abnormalities exist in highly oxidative muscle beds of healthy aged individuals, as has been demonstrated in rodent models (46,66). As norepinephrine and phentolamine are nonselective ␣-adrenergic agonists and an-tagonists, respectively, these results do not preclude a possible differential effect of aging on ␣ 1 -or ␣ 2 -adrenergic-mediated blood flow regulation.…”
Section: Discussionmentioning
confidence: 94%